Challenges in Maintaining Professionalism Amid Educational Dynamics - Nugraha, Muthia Hanifa; Rivaldi, Muhamad; Salsabilah, Lulu; Yudistira, Muhamad Bambang (PGMI, STAI Miftahul Ula Nganjuk, 2025)
Humans are regarded as Homo Educandum, in which teachers hold a key role in the success of the learning process and character formation in education. However, amid the continuously evolving dynamics of education, teachers face various challenges in maintaining their professionalism. This study aims to examine these challenges, including curriculum changes, the integration of digital technology, and student diversity, as well as strategies that can be implemented to enhance teacher professionalism. The research approach employed is a literature review, conducted by collecting and analyzing various reliable sources of information such as academic journals, books, and educational policy documents. The findings indicate that teachers need to improve their pedagogical competence, technological adaptability, and inclusive approaches to meet the demands of a dynamic educational environment. The recommendations proposed include continuous professional development, collaboration among teachers, and the strengthening of the four prerequisites of teacher professionalism according to Samani. Thus, well-maintained teacher professionalism will have a positive impact on the quality of education and the future of the nation’s next generation.